REINTERPRETASI TERHADAP HADIS UNTUK MENGEMBALIKAN HAK POLITIK PEREMPUAN - Tasbih,; A. Hafid, Saidah (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2023)
The restriction on the role of women in public life is due to a number of images built about negative attitudes towards women. The set of attitudes, roles, responsibilities, functions, rights, and behaviors inherent in women is often based on the understanding of hadith as one of the sources of Islamic law. This study examines how to reinterpret hadith to restore women's political rights. This qualitative study is a literature review. The data is obtained from recent references that highlight injustice against women, especially in the world of Islamic politics. The results of the analysis show that reunderstanding political hadiths with several points of view will restore women's political rights. Misconceptions of hadith have marginalized women from the Islamic political world for hundreds of years. These findings may contribute to the nuances of future hadith studies.